1976
DOI: 10.1111/j.1399-3054.1976.tb03987.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of Oxygen‐evolving System in Dark‐grown Spruce Seedlings

Abstract: Plastids prepared from dark‐grown spruce seedlings showed a negligible activity of photosystem II, and no fluorescence variation was observed during actinic illumination. The photosystem II reaction centre, however, was present in primary thylakoids. Exposure of such seedlings to continuous light induced the development of photosystem II activity via three stages (rapid, lagged and gradual), and the variable fluorescence appeared. The rapid development of photosystem II may be attributed to the activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Photoactivation of the water-oxidation system has been widely reported for Imf3 angiosperm leaves (11,23), dark-grown gymnosperm leaves (16), dark-grown algal cells (7), Mn-deficient algal cells (5), NH20H-extracted cyanobacterial cells (6), and Tris-extracted chloroplasts (26). The process can be driven by continuous light or by a series of short (as) flashes with intervals of a few seconds, indicative of the involvewr Xnt of a multiquantum process (6,7,11).…”
mentioning
confidence: 99%
“…Photoactivation of the water-oxidation system has been widely reported for Imf3 angiosperm leaves (11,23), dark-grown gymnosperm leaves (16), dark-grown algal cells (7), Mn-deficient algal cells (5), NH20H-extracted cyanobacterial cells (6), and Tris-extracted chloroplasts (26). The process can be driven by continuous light or by a series of short (as) flashes with intervals of a few seconds, indicative of the involvewr Xnt of a multiquantum process (6,7,11).…”
mentioning
confidence: 99%
“…All of the photoactivation studies reported to date have been performed by using PSII cores (26), PSII membranes (19,20), or larger, native-like preparation (18,27,28). The possibility of oxygen evolution from smaller PSII subcore complexes has not been demonstrated previously, although Rögner et al (29) had shown that a PSII complex can form within the photosynthetic membrane in a CP43 deletion mutant of Synechocystis that This paper was submitted directly (Track II) to the PNAS office.…”
mentioning
confidence: 99%
“…Stringent conditions for the in situ hybridization were determined by hybridizing the probes with pine chloroplasts (27), cells of pine-associated bacteria (the bacteria under study and Mycobacterium sp. [21]), and two control bacteria (E. coli DH5␣ and Lactobacillus delbrueckii subsp.…”
mentioning
confidence: 99%